معايير تقويم موافع تعليم اللغة العربية وتعلمها بوصفها لغة ثانية : من خلال ثلاثة مواقع تعليمية - Nor Aishin Nada binti Ahmad Rashidi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study seeks to clarify the standards of evaluating Arabic as a second language in website for teaching and learning. In this study, the researcher chose descriptive, analytical and evaluation approaches to study the specific educational sites on the Internet. This study was conducted in order to know the standards that should be implemented and used by the designers while designing websites for teaching Arabic as a second language. It is because non-observance of these standards will lead to an imbalance and lack of action while the sites are created for educational purposes. Thus, these sites will bring negative effects on learners and teachers instead of positive effects on the processes of learning. This study indicates that quality standards are very important during the construction, design and evaluation of educational websites. The researcher prepared a set of questionnaire containing ten standards on information and references through books, previous studies and expert and specialist reviews on web-designing, especially in the educational programme for teaching Arabic as a second language. The result shows that cronbach's alpha to identify the questionnaire value was reached at ٠٫٩٣٥ which indicates that this questionnaire was valid and usable. This questionnaire was applied in three selected educational websites; Arab Academy website, Open University website and Medina International University website. The mean values for the Arab Academy website and the Medina International University website were ٤٫٢, and for the Open University Malaysia website was ٢٫٢. The general evaluation shows that Arab Academy website mean value was ٤٫٧٥, Open University Malaysia website was ٤٫٥, and Medina International University was ٤٫٢٥. These results indicate that the use of these standards will support the effectiveness of teaching Arabic as a foreign language and improve the ability of teachers and learners to deal with this language. The three sites mentioned are valid for educational purposes in general.